Dedifferentiated Liposarcoma: Updates on Morphology, Genetics, and Therapeutic Strategies. (January 2016) - Thway, Khin; Jones, Robin L.; Noujaim, Jonathan; Zaidi, Shane; Miah, Aisha B.; Fisher, Cyril
Abstract : Well-differentiated liposarcoma (WDL) and dedifferentiated liposarcoma (DDL) form the largest subgroup of liposarcomas, and represent a morphologic and behavioral spectrum of 1 disease entity, which arises typically in middle to late adult life, most frequently within the retroperitoneum or extremities. DDL is defined as nonlipogenic sarcoma that is juxtaposed to WDL, occurs as a recurrence of WDL or which can arise de novo, and typically has the appearance of undifferentiated pleomorphic or spindle cell sarcoma. DDL have a propensity for local recurrence, whereas distant metastasis is rarer, and behavior is related to anatomic site, with retroperitoneal neoplasms showing a significantly worse prognosis. Surgical resection remains the mainstay of treatment, and medical options for patients with aggressive recurrent or metastatic disease are limited. DDL share similar genetic abnormalities to WDL, with high-level amplifications of chromosome 12q14-15, including the MDM2 and CDK4 cell cycle oncogenes, and DDL harbor additional genetic changes, particularly coamplifications of 6q23 and 1p32. Novel therapies targeted at the gene products of chromosome 12 are being tested in clinical trials. We review the pathology and genetics of DDL, discussing morphologic patterns, immunohistochemical and genetic findings, the differential diagnosis, and future therapeutic strategies.